2013
DOI: 10.1155/2013/352621
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Gingival Health Status among 5- and 12-Year-Old Children in Yemen: A Cross-Sectional Study

Abstract: Purpose. There are limited data about the gingival health status in Yemeni children. The aim, therefore, was to assess oral hygiene status and prevalence and severity of gingivitis among Yemeni preschool and school children. Materials and Methods. A total of 5396 children were included from 5 representative Yemeni governorates: Sana'a, Hajjah, Hodeida, Hadramaut, and Taiz. Five-year olds (1292) were recruited from private kindergartens while 12-year olds (4104) were selected from public primary schools. Gingiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 21 publications
(27 reference statements)
5
23
2
Order By: Relevance
“…However, some previous reports showed opposite results. 12,18,24 The current study found that 12-year-old children had more calculus accumulation than 6-year-old children. It appears that children 12 years of age are 1.65 times more likely to have calculus deposits than 6-year-old children.…”
Section: Discussionmentioning
confidence: 44%
See 4 more Smart Citations
“…However, some previous reports showed opposite results. 12,18,24 The current study found that 12-year-old children had more calculus accumulation than 6-year-old children. It appears that children 12 years of age are 1.65 times more likely to have calculus deposits than 6-year-old children.…”
Section: Discussionmentioning
confidence: 44%
“…Another possible factors might be the culture, food habits, and geographical location that act as independent determinant. 12 There was no significant difference between the 6-year-old group and the older age group in relation to the mean of PI and GI. This result differs from previous reports.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations